Islamic Center di Kota Malang - Listyaningtyas, Fitriyah; Trimarianto, Ciptadi; Wiryawan, I Wayan (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas Udayana, 2021)
The growth of Muslims is inseparable from the existence of social facilities related to religious activities which function as a forum for Muslims to carry out spiritual development. These facilities are generally is a mosque, wherein carrying out its functions there are often restrictions on activities that only rotate in worship and da’wah. Therefore, it is necessary to design an Islamic center as a center for Islamic activities to facilitate the empowerment of the people in the scope of education, social cultural, and economy in a directed and sustainable manner. Religious facility buildings generally display a reaction to the uniformity of Islamic architecture, which weakens the local architecture position. In designing the Islamic Center in Malang City, it uses a regionalism architectural approach. Local values used in buildings are values that do not conflict with Islamic teachings. The main building at the Islamic Center applies locality values acculturated to Islamic values and displayed in the zoning, form of buildings, materials use, and decorations. Keywords: Islamic Center, Islam, architecture regionalism.